PARTICIPATION IN PHYSICAL CULTURE AND HEALTH EDUCATION – SELECTED ISSUES - Skalski, D. W.; Kowalski, D.; Graczyk, M.; Rybak, O.; Kindzer, B.; Kyryk, O. (Rehabilitation and Recreation, 2022)
Making children believe that health is an asset and a value that is worth caring for and striving for, is one of the most important goals of health education. Kindergarten and school play an important role in shaping positive attitudes of children, including those promoting health, and health education should be analyzed as a basic right of every child, which should be included in their preschool and early childhood education. Issues related to health education carried out in educational and upbringing institutions are of interest to a small group of authors. In the available publications, one can notice a specific lack of focus on pre-school and early-school health education issues from a systemic perspective. Therefore, there is a need to attempt to fully comprehend the issues of preschool and early childhood health education, which has been attempted in this study. Health education activities should be started as early as possible, as engaging in quality education in the first years of a child's life is much more effective and brings significant benefits later in life than later interventions. Therefore, bearing in mind its importance, this education cannot be omitted at the stage of pre-school and early school education. In health education, the most important concept, both for theoretical considerations and for practical solutions based on them, is health. The concept of health may be the subject of reflection of at least three sciences: medicine, psychology and sociology. Physical education and sport at school, due to the sports activation of a huge group of children and adolescents, is extremely important in the social and individual dimension. This activity has a direct impact on the physical and mental condition of the young generation. It improves the health of our society and builds habits of physical activity, which is an essential element of our health in every age group. In summary, physical activity and health education are of great importance for health. Avoiding them can lead to disturbances in the functioning of the body, which results in diseases. If we spend our free time actively, it will bring many benefits for us, not only physically, but also mentally, we will better cope with stress.